Survival and risk factors for metastatic colorectal cancer patients with a history of prior malignancy - Yiwen Qiu; Nida Cao; Dan Meng; Jian Yuan; Yingjie Zhu (Scientific Reports)
Abstract Given concerns about treatment, there is uncertainty surrounding the effect of prior malignancy on the survival of individuals with metastatic colorectal cancer. This study sought to evaluate how prior malignancy impacts the survival of patients with metastatic colorectal cancer (mCRC). Patients diagnosed with stage IV mCRC (per the American Joint Committee on Cancer [AJCC] 6th edition) between 2004 and 2015 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Those without a prior history of malignancy were assigned to the control group, whereas those with a prior history of malignancy were assigned to the research group. Propensity score matching (PSM) was utilized to ensure that the baseline characteristics were balanced. The Kaplan‒Meier method was used for survival analysis, as were the multivariate Cox proportional hazard model and multivariate competing risk model. The PSM analysis included 54365 eligible patients with mCRC. Among them, 4,845 (8.9%) had a history of prior malignancy. A history of prior malignancy was associated with a greater cancer-specific survival rate (adjusted hazard ratio (AHR) ) = 0.49; 95% CI [0.47–0.51]). Subgroup analyses revealed that a prior diagnosis of a skin tumour (AHR = 1.37; 95% CI [1.11–1.69]) and a history of prior malignancy of more than five years (AHR = 1.39; 95% CI [1.23–1.57]) had adverse effects on the clinical outcomes of patients with mCRC. Our findings suggest that patients with a prior malignancy diagnosis may experience prolonged survival. Subgroup analysis indicated that a malignancy diagnosed more than 5 years ago may adversely impact the clinical outcomes of patients with mCRC. Therefore, we advocate for active standardized treatment for these patients and propose expanding the range of prior malignancies included in clinical trials based on publication timelines, primary tumour locations, and genetic testing results. The objective is to facilitate timely and proactive treatment for patients following the disclosure of results, thereby instilling confidence in the management of mCRC.